Impact of Sex on Office White Coat effect Tail: A Review - Humbert, Xavier; Fedrizzi, Sophie; Hofferer, Agnès; Bansard, Mathieu; Huet, Anne-Laure; Bedier, Christiane; Rabiaza, Andry; Bas, Jeanne L.; Bas, François L.; Alexandre, Joachim; Puddu, Paolo E. (Current Pharmaceutical Design, 2021)
Office white-coat effect tail (OWCET) is defined as a decrease of ≥10 mmHg in systolic blood pressure (SBP) between successive measurements after its waxing during an office visit. The influence of sex on the incidence of long-term major fatal and non-fatal cardiovascular events was studied in two Italian populational cohorts [from the Gubbio Study and the Italian Rural Areas of the Seven Countries Study (IRA)]. OWCET increased risk of cardiovascular disease (CVD) [HR: 1.591 (95% CI: 1.204-2.103)], coronary heart disease (CHD) [HR: 1.614 (95% CI: 1.037-2.512)] and stroke (STR) [HR: 1.696 (95% CI: 1.123-2.563)] events independently of age, serum and high density lipoprotein (HDL) cholesterol, cigarettes, body mass index (BMI) and SBP in women included in Gubbio study over an almost 20-year follow-up. However, risks of CVD, CHD or STR increased in men with OWCET neither in the Gubbio 20-year follow-up nor in the IRA 50-year follow-up. The correction of the regression dilutions bias between the first and the subsequent SBP measurements did not significantly change these outcomes. Primary care physicians should evaluate OWCET, especially in women, to improve stratification of long-term CVD, CHD and STR risks.
Keywords: sex